Clinical management and therapeutic diagnosis of a presumptive case of canine immune-mediated hemolytic anemia - Solano-Rodríguez, José Pablo (2015)
Autoimmune diseases (AID) continue to represent a major diagnostic challenge to veterinary practitioners and can be easily confused with other pathologies. It is the intent of this paper to exemplify this situation using a presumptive case of autoimmune hemolytic anemia, one of the most frequent autoimmune diseases in dogs. This case was referred to the Hospital for Wild and Minor Species from the School of Veterinary Medicine at Universidad Nacional (Costa Rica).A seven year old female Australian Shepherd was admitted for a blood transfusion with a presumptive diagnosis of canine ehrlichiosis. However, based on lab results and the physical examination, a diagnostic of canine autoimmune hemolytic anemia was suspected. The patient was hospitalized for thirteen days and received the appropriate treatment according to the current literature.  The patient´s evolution and response to therapy were monitored. The patient was discharged and eight months later neither adverse effects to the therapy nor recurrence of the disease were reported.